Body as machine: Health vulnerability of women garment factory workers in India - Arima Mishra; Rajesh Joseph; Manjunath Gangadhara; Roshni Lobo (Elsevier, 2023)
Even though garment factory work has attracted women in large numbers in urban and peri-urban settings in low- and -middle income countries including India, there is relatively limited health system research on identifying and addressing the health vulnerability of this workforce. Drawing on data on life histories of women workers (n ​= ​16), semi-structured interviews with others including family members of deceased workers, health professionals, members of the labor union, factory management (n ​= ​15), focus group discussions with women garment workers (n ​= ​04) and observations (n ​= ​04) of workplaces including export as well as domestic factory units and women labor union activities, we discuss how women's talk on 'health' traverses through different layers and sites of silences. Women highlighted the narratives around menstruation ('less', 'more', 'infrequent', 'irregular' and related reproductive health consequences) as one of the important ways to talk about relationships between their body, work, and health. Predominantly for them, 'bodily heat' and 'torture' emerged as two important expressions that describe their everyday vulnerability to health. These narratives call for greater research and policy attention to the large women workforce in the garment factories who remain invisible to the health system. More importantly, it points towards the need for incorporating qualitative research methodologies in occupational health and safety discussions to foreground the perspectives and experiences of workers themselves.